Investments analysis and decision making: valuing R&D project portfolios using the PROV exponential decision method - Rocha, António Miguel Sousa (2014)
To support the assessment of R&D project portfolios and to establish a systemic model to carry multiple evaluations using the decision-maker knowledge, preferences and purposes we have developed an evaluation matrix and a new procedure based on the PROV exponential decision method which uses multiple utility functions modeled to establish a common framework from which we can determine the projects relative value. The presentation of this new procedure is the main focus of this article and numerical examples are presented to illustrate the proposed approaches to attain comprehensible results and to discover the most valuable R&D projects to support investment decisions.